Neurobiological correlates of reactive aggression in young adults with internet gaming disorder - Shijie Chen; Hongwei Hong; Yuhong Zhou; Xinyu Huang; Xuemei Gao (Brain Research Bulletin)
Background: Previous research has found a significant positive correlation between internet gaming disorder (IGD) and reactive aggression (RA), with excessive use of online games increasing aggression in subjects. However, the neural mechanisms underlying increased RA in IGD are unclear. This study explores the neurobiological underpinnings of reactive aggression in young adults with IGD. Method: This case-control study included 84 young adults, comprised of 23 subjects with IGD, 24 at-risk participants, and 37 healthy controls. Employing T1-weighted magnetic resonance imaging (MRI), voxel-based morphometry (VBM) analysis was conducted to evaluate the gray matter volume (GMV) changes among groups, and the partial correlations between GMV alterations and RA score were investigated. Finally, mediation analyses were conducted to examine whether GMV alterations could modulate the relationship between IGD degree and RA score. Results: Compared with controls, the IGD group showed significantly increased GMV in the middle frontal gyrus (MFG), parahippocampal gyrus and significantly decreased GMV in the right median cingulate and paracingulate gyri (DCG), while the at-risk group showed significantly increased GMV in the left MFG. In addition, the RA score showed a significant negative correlation (r=-0.301, p=0.006) with the mean GMV of the right DCG. Furthermore, the mean GMV of the right DCG significantly mediated the correlation between degrees of IGD and RA score, and the effect size for this mediation effect was 22.8 %. Conclusion: Our findings provide potential early risk biomarkers for IGD and enhance our understanding of the neurobiological mechanisms linking RA to IGD, thus facilitating several potential avenues for therapeutic intervention.